Pendampingan Penyusunan Administrasi PAUD Sekato Desa Mandiangin Kecamatan Minas Kabupaten Siak - Ida Windi Wahyuni; Ary Antony Putra (Jurnal Pengabdian Pada Masyarakat, 2020)
ASSISTANCE IN PREPARING PAUD SEKATO ADMINISTRATION OF MANDIANGIN VILLAGE, MINAS DISTRICT, SIAK REGENCY. Educational administration there are several fields or elements that are interrelated with one another, namely the field of human resources, learning resources, and facilities implemented. These three elements are listed in one system which is divided into three functions, namely the planning function, the implementation function, and the supervisory function. PAUD administration assistance directs school principals, teachers and PAUD program development in carrying out technical guidance in administering PAUD institutions. The purpose of the activities to be carried out in this activity is to evaluate and arrange school administration and curriculum in PAUD Sekato as well as to assist in preparing PAUD administration. Assistance in the preparation of PAUD administration is carried out in PAUD Sekato, Mandiangin Village, Minas Subdistrict, Siak Regency, from July to August 2019. The results of this activity are the preparation of PAUD administration. Sekato Mandiangin Village only focuses on general administration, learning administration and student administration. The limitations of this assistance are due to the time, distance and available funds. The team hopes for the next program is to prepare an administrative program that has not yet been completed so that the administration of Sekato PAUD is completely arranged and can be submitted in the PAUD accreditation submission.